Ovarian cancer: emerging concept on cancer stem cells - Ponnusamy Moorthy P; Batra Surinder K (BMC, 2008)
Abstract Emerging evidence suggests that the capacity of a tumor to grow and propagate is dependent on a small subset of cells within a tumor, termed cancer stem cells. In fact, cancer cells, like stem cells, can proliferate indefinitely through a dysregulated cellular self-renewal capacity. Cancer stem cells may originate due to the distribution into self-renewal and differentiation pathways occurring in multi-potential stem cells, tissue-specific stem cells, progenitor cells and cancer cells. Recent studies have shown that ovarian cancer also contains stem cells or tumor-initiating cells. Moreover, ovarian serous adenocarcinomas were disaggregated and subjected to growth conditions to select for self-renewing, non-adherent spheroids previously shown to be derived from tissue stem cells. A recent study showed that epithelial ovarian cancer was derived from a sub population of CD44+, CD117+ and CD133+ cells. The existence of cancer stem cells would explain why only a small minority of cancer cells is capable of extensive proliferation of the tumor. In this review, we have discussed the studies on ovarian cancer stem cells along with the molecular pathways that could be involved in these cancer stem cells.